Analisis Perhitungan Rencana Anggaran Biaya (Rab) Pada Jalan Tani Kelurahan Gurabati - Yusuf, Siti Rahmawati; Muhammad, Amiruddin Hi.; Altarans, Indra (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study analyzes the Budget Plan (RAB) calculations for farm road construction in Gurabati Village by comparing flexible pavement and rigid pavement. The methods used include work volume calculations and unit price analysis (AHSP) using Microsoft Excel. The results indicate that the construction cost of flexible pavement is Rp 1,340,350,000, while that of rigid pavement is Rp 1,891,450,000. Based on the analysis of construction costs and long-term maintenance, flexible pavement is more economical to implement. This research can serve as a reference for efficient and tailored farm road construction planning.